2017
DOI: 10.1080/1120009x.2017.1380357
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of oral antibiotics for the treatment of uncomplicated urinary tract infections

Abstract: The therapeutic management of uncomplicated bacterial urinary tract infections (UTIs) is based on short-term courses of oral antibiotics. The preferred drugs are nitrofurantoin trimethoprim-sulfamethoxazole, fosfomycin trometamol, fluoroquinolones and β-lactam agents. The choice of agent for treating uncomplicated UTIs should be based on the pharmacokinetic characteristics of the molecule so that clinical benefit is optimized and the risk of antibacterial resistance is minimized. This article discusses the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 71 publications
1
26
0
3
Order By: Relevance
“…After the first dose, a high urinary concentration is maintained for 3 days. It is a single-dose treatment regime with clinical activity and safety in the management of noncomplicated UTIs [17].…”
Section: Discussionmentioning
confidence: 99%
“…After the first dose, a high urinary concentration is maintained for 3 days. It is a single-dose treatment regime with clinical activity and safety in the management of noncomplicated UTIs [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has a broad-spectrum antibacterial activity, including Gram-positive and ESBL-producing gram-negative strains. FT has good in vitro activity against many multidrug resistant uropathogen species [12]. FT is an attractive drug in the treatment of UTI by means of certain properties including rapid absorption after oral administration and achieving high urine concentration, biofilm activity and efficacy against various multidrug-resistant organism such as extended spectrum beta-lactamase-(ESBL) and AmpC beta-lactamase-(AmpC) producing Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Oral FT is well tolerated and has no serious side effects. Only 5% of patients are reported to have side effects, most commonly diarrhea [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The oral bioavailability of TMP/SMX is 85%‐90%, and there is a long‐standing experience with its use in children with severe infections including those with PJP and S aureus osteomyelitis, even if controversially discussed . Moreover, it has been demonstrated that gastrointestinal damage induced by chemotherapy does not affect the bioavailability of TMP‐SMX, further confirming the safety of this type of administration in this patients’ population.…”
mentioning
confidence: 87%
“…[13][14][15] Meanwhile, we observed 1 possible, not confirmed case of CNS-T after an allogeneic SCT with disseminated chronic GvHD. 16 The oral bioavailability of TMP/SMX is 85%-90%, 17 and there is a long-standing experience with its use in children with severe infections including those with PJP 18 and S aureus osteomyelitis, 19 even if controversially discussed. 20,21 Moreover, it has been demonstrated that gastrointestinal damage induced by chemotherapy does not affect the bioavailability of TMP-SMX, 22 23 and therefore is plausible also in these cases.…”
mentioning
confidence: 99%